EMPOWERMENT STRATEGIES FOR THE COMMUNITY’S ECONOMY THROUGH THE CENTER OF SHARIA BUSINESS INCUBATION (PINBAS) OF INDONESIAN ULAMA COUNCIL NORTH SUMATERA IN ALLEVIATING POVERTY - Frida Yanti Sirait; Sri Sudiarti; Tuti Anggraini (Universitas Tidar, 2024)
The Center of Sharia Business Incubation (PINBAS) of the Indonesian Ulama Council (MUI) plays a significant role in developing and promoting businesses that comply with Sharia economic principles to promote the community’s self-sufficiency in alleviating poverty. Yet, the effective strategies for empowering the people's economy are still far from MUI's expectations. The community’s economic empowerment requires more creative efforts and smart work to reveal an adequate solution. The research aims to analyze strategies for community economic empowerment employed by PINBAS of MUI North Sumatera chapter in alleviating poverty. The SWOT analysis and QSPM are applied as research methods. The number of respondents was 6 people and 5 people, respectively. Respondents were appointed based on their understanding of economic empowerment among academics and practitioners. The results obtained from the SWOT analysis recommend the alteration of strategies in quadrant III, 1) So far, the strategies that have been carried out are designated to increase public knowledge and awareness, partnerships with sharia financial institutions, collaboration and innovation, and research. 2) Factors of strengths, weaknesses, opportunities, and threats, namely creating cooperation programs with other parties, Helping to run government programs to assist in the form of capital training and appropriate human resources, Creating new markets, Maximizing support, Providing promising good results and Providing training programs to the community 3) Urgency of Handling future Internal and External Factors by providing promising results so that they understand sharia business principles in detail, Collaborating with various parties, Overcoming limited available resources, Providing training programs to the community by documenting and sharing them with mass media. 4) The main priority strategy that needs to be implemented is to provide training programs to the community by documenting and sharing them with the mass media so that common people will be aware of the existence of these programs and more people will taking part in the programs. 5) Economic empowerment model community activities carried out by PINBAS in overcoming poverty, namely entrepreneurship/mapping data, creativity patterns (business/figure inspiration), and nurturing togetherness.